PENGARUH VARIASI CAMPURAN OCTANE BOOSTER TERHADAP EMISI GAS BUANG ENGINE STAND HONDA BRIO - Ryan Pradana Putra (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The increasing number of motor vehicles in Indonesia has raised fuel consumption and exhaust emissions that pollute the air. Octane boosters are believed to improve combustion quality and thereby reduce the exhaust emissions of gasoline engines. This study aims to determine the effect of low-cost octane booster mixture variation on CO, CO₂, and HC exhaust emission levels of a Honda Brio engine stand (1,198 cc SOHC i-VTEC). An experimental method with a Posttest Only Control Group Design was applied, consisting of four treatment groups: pure Pertalite fuel (K0) and Pertalite mixed with octane booster at doses of 5 ml/L (K1), 10 ml/L (K2), and 15 ml/L (K3). Emission measurements were taken using a gas analyzer with three repetitions per group. The results show that octane booster addition reduced CO levels from 7.00% (K0) to 6.70% (K3) and HC levels from 694 ppm (K0) to 480 ppm (K3), while CO₂ levels increased from 5.9% (K0) to 6.3% (K3). The most significant emission reduction occurred within the 5-10 ml/L dose range, and the 15 ml/L dose produced the best emission results among the tested variations. These findings indicate that adding a low-cost octane booster improves the combustion process of the Honda Brio engine and has potential to be integrated as a contextual learning medium in automotive engineering education.